2010
DOI: 10.1016/j.jhazmat.2010.07.082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fireworks events on urban background trace metal aerosol concentrations: Is the cocktail worth the show?

Abstract: We report on the effect of a major firework event on urban background atmospheric PM(2.5) chemistry, using 24-h data collected over 8 weeks at two sites in Girona, Spain. The firework pollution episode (Sant Joan fiesta on 23rd June 2008) measured in city centre parkland increased local background PM(2.5) concentrations as follows: Sr (x86), K (x26), Ba (x11), Co (x9), Pb (x7), Cu (x5), Zn (x4), Bi (x4), Mg (x4), Rb (x4), Sb (x3), P (x3), Ga (x2), Mn (x2), As (x2), Ti (x2) and SO(4)(2-) (x2). Marked increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 26 publications
1
41
0
1
Order By: Relevance
“…The background concentration refers to the measurements carried out along the week in periods when mascletà peaks did not take place and should represent the city "normal" concentrations. The concentrations we found are higher than those found in other studies [4,10,17] and for many elements similar to the ones found by Kuhlteshta et al and Sarkar et al for Diwali festival [6,18] and Wang et al for Lantern Festival [5] (our data were averaged in the same time scales used in the cited article).…”
Section: Elemental Concentration With One-hour Temporal Resolutionsupporting
confidence: 88%
See 2 more Smart Citations
“…The background concentration refers to the measurements carried out along the week in periods when mascletà peaks did not take place and should represent the city "normal" concentrations. The concentrations we found are higher than those found in other studies [4,10,17] and for many elements similar to the ones found by Kuhlteshta et al and Sarkar et al for Diwali festival [6,18] and Wang et al for Lantern Festival [5] (our data were averaged in the same time scales used in the cited article).…”
Section: Elemental Concentration With One-hour Temporal Resolutionsupporting
confidence: 88%
“…Barium and strontium salts are used as colour agents, imparting a red or green colour, respectively, to firework displays. They are also important for stabilising fireworks and barium nitrates or chlorates as oxidiser too [4,10]. Sr and Ba, elements with still lower background concentrations (<10 ng/m 3 ), reached concentration peaks during mascletàs up to 16 and 10 g/m 3 in the fine fraction, respectively, and about 1.5 g/m 3 in the coarse fraction.…”
Section: Elemental Concentration With One-hour Temporal Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BC concentration was only 1.8% of the PM 2.5 concentration during the episode period, and the BC/PM 2.5 ratio was 5.5% in the nonepisode period. Past results have indicated that a relatively large amount of other compounds exist in the aerosols produced by a firework display (Wang et al, 2007;Moreno et al, 2010;Chang et al, 2011;Lin et al, 2014). For example, Chang et al (2011) and Lin et al (2014) found that the aerosols produced were remarkably high in Cl -, K + , and Mg 2+ ions compared with the background aerosols.…”
Section: Meteorological Conditions During the Beehive Firework Displamentioning
confidence: 99%
“…For example, Chang et al (2011) and Lin et al (2014) found that the aerosols produced were remarkably high in Cl -, K + , and Mg 2+ ions compared with the background aerosols. Wang et al (2007) and Moreno et al (2010) demonstrated that concentrations of elements such as Sr, Mg, K, Ba, and Cu were far greater in airborne dust during firework episodes. The presence of these highly toxic metals was related to the materials used in the fireworks.…”
Section: Meteorological Conditions During the Beehive Firework Displamentioning
confidence: 99%